Ninth Five Year Plan 1997-2002 Volume II Thematic Issues and Sectoral Programmes - Planning Commission, Government of India (Planning Commission, Government of India, 1997)
The objectives of the Ninth Plan have been spelt out in the Approach to the Ninth Five Year Plan document adopted by the National Development Council. “Growth with Social Justice and Equity” is proposed to be achieved with the objectives outlined in the Approach Paper. Some specific areas from within the broad objectives of the Plan as laid down by the NDC have been selected for special focus. For these areas, Special Action Plans (SAPs) have been evolved in order to provide actionable, time-bound targets with adequate resources. Broadly, the SAPs cover specific aspects of social and physical infrastructure, agriculture, information technology and water policy.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Ninth Five Year Plan- India; Economic development